AUTOEVALUACIÓN, PLAN DE MEJORAS Y EFICACIA ACADÉMICA EN LA FACULTAD DE CIENCIAS ADMINISTRATIVAS DE LA UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS - Vigo Sánchez, Edwin Augusto (2014)
This research has the purpose of contributing to the achievement of the accreditation of the school of Sciences administrative from San Marcos University, within the framework of the law of the SINEACE No. 28740, law on the national system of evaluation of the quality of education, responsible for standardizing the processes of evaluation, accreditation and certification of the quality of education in our country. a process of self-assessment should lead to a subsequent accreditation and certification by the faculty, entails the development, analysis and feedback related to the practices pre professionals, skills acquired by students and graduates, methodology for the evaluation and monitoring of learning; administrative organization, complementary academic services, structure physics and equipment. The self-assessment is a process of analysis critical of academic and faculty administrative areas, units that precedes the accreditation. Accreditation is a procedure, whose objective is to compare the degree of approach of the object analyzed with a set of rules previously defined and implemented as desirable. The Faculty of sciences administrative of the University National chief of San Marcos aims to train competent professionals and high level academic, committed to the development of the country through the research scientist and humanist and the preservation of the environmental conservation.